Novel therapeutic approaches for uveitis and retinitis - Thilek Kumar M.; Pandit J.K.; Balasubramaniam J. (My University, 2025)
A virtual increase in the number of patients undergoing immunosuppressant therapy and those suffering from AIDS has created a unique class of population suffering from virulent uveitis and retinopathies. A very common pathogen implicated in retinopathy in such patients is the cytomegalovirus (CMV).